Educational Game-Based Thematic Learning Media to Improve Student Learning Competence - Yenni mesilina Haloho; I Kadek Suartama; I Komang Sudarma (Universitas Pendidikan Ganesha, 2023)
The limitations of interesting learning media on thematic subjects impact low student learning competence. To improve student learning competence, digital learning media is needed that is easy for students to access. This study aims to develop educational game-based thematic learning media to improve the learning competence of grade IV students. This research is developmental research using the Hannafin & Peck model. The research subjects were one content expert, one design expert, and one learning media expert, then three individual trials, six small group trials, and fifteen field trials. Data collection in this study was carried out using questionnaires and tests, with research instruments in the form of product validity test questionnaires and student learning outcomes tests. The data obtained in the study were then analyzed using quantitative descriptive analysis techniques and qualitative descriptive analysis methods. The research analysis results showed that the products developed were valid based on the results of content experts obtained at 95.50%, learning design experts obtained at 88.00%, learning media experts at 94.67%, individual trials at 92.67%, small group trials at 95.17%, and field trials 95.70%. Based on these results, it can be concluded that developing educational games in thematic subjects in class IV is classified as a very good qualification and is declared suitable for use in the learning process.